Tradisi ‘Mupu’ Dalam Perspektif Al-Qur’an dan Pengembangan Nilai Moderasi Beragama Dalam Upaya Pembentukan Keluarga Harmonis (Kajian Tafsir Maqashidi) - Fahimah, Siti; Nihlah, Wakhidatun; Diyanah, Lubabah (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research will take the object of the mupu tradition of 'mupu' or child adoption in framing religious moderation towards a harmonious family or Sakinah which is aligned with the views of the Koran. The aim of this research is to provide an explanation of the application of the principles of religious moderation which can be applied to frame a harmonious family through the 'mupu' tradition and the problems in implementing child adoption in terms of Islamic law contained in the Koran. The research uses qualitative research based on library research with the Maudhui interpretation method, the Maqasidi approach. The results of this research are first, that the practice of 'mupu' children can be used as a solution to overcome the problem of family disharmony for those who have the weakness of not having children by implementing tawasuth (the Middle Way) and shura or mutual consultation between husband and wife and family), secondly, it is forbidden for someone to name or call an adopted child to someone other than his father. However, it is permissible if this is due to someone's ignorance. Adoption or 'mupu' was already practiced by the Prophet Muhammad, namely adopting Zaid bin Haritsah as his own son.